2016
DOI: 10.1111/jbi.12922
|View full text |Cite
|
Sign up to set email alerts
|

Fine‐scale demographic processes resulting from multiple overseas colonization events of the Japanese stream tree frog, Buergeria japonica

Abstract: Aim Amphibians are considered poor transoceanic dispersers because of their permeable skin. However, overseas dispersal of amphibian species has been revealed by recent phylogeographical studies and the role of overseas colonization of amphibians on their evolution and diversification has also been highlighted. However, no studies have investigated in detail the demographic processes related to these overseas colonization events. To clarify how amphibians achieve overseas colonization, we estimated the demogra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
12
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 49 publications
(71 reference statements)
2
12
0
Order By: Relevance
“…Despite the lack of empirical evidence, several Taiwanese reptiles have been posited to colonize from the Malay Archipelago by oversea dispersal (Hsiang et al, 2009). Evidence from the Taiwan-Ryukyu Islands (Komaki et al, 2017;Yang et al, 2018) and the Taiwan-Luzon Islands (Esselstyn & Oliveros, 2010) has also supported oversea dispersal as a potential mechanism for the geographical origin of insular vertebrates. Accordingly, we suggest that prior to the emergence of the Pleistocene land bridge; Taiwan might have provided virgin habitat such as newly formed oceanic islands for the pioneers derived from the mainland via oversea dispersal.…”
Section: Temporal Origin Of Taiwanese Faunamentioning
confidence: 98%
See 1 more Smart Citation
“…Despite the lack of empirical evidence, several Taiwanese reptiles have been posited to colonize from the Malay Archipelago by oversea dispersal (Hsiang et al, 2009). Evidence from the Taiwan-Ryukyu Islands (Komaki et al, 2017;Yang et al, 2018) and the Taiwan-Luzon Islands (Esselstyn & Oliveros, 2010) has also supported oversea dispersal as a potential mechanism for the geographical origin of insular vertebrates. Accordingly, we suggest that prior to the emergence of the Pleistocene land bridge; Taiwan might have provided virgin habitat such as newly formed oceanic islands for the pioneers derived from the mainland via oversea dispersal.…”
Section: Temporal Origin Of Taiwanese Faunamentioning
confidence: 98%
“…Brown et al, 2013;Crottini et al, 2012;de Bruyn et al, 2014;Stelbrink, Albrecht, Hall, & von Rintelen, 2012). Nevertheless, studies on East Asian islands are comparatively limited, and due to the distinct geological contexts, the biogeographical patterns on East Asian islands are rather distinct (Li, Fu, & Lei, 2011;Komaki et al, 2017;Su, Brown, Chang, Lin, & Tso, 2016;Yang, Komaki, Brown, & Lin, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The identification of factors leading to speciation and elucidation of the associated mechanisms generating biodiversity are considered to be important tasks by evolutionary biologists (Schluter & Pennell, ). Previous studies targeting various taxa demonstrated that the origins of genetic diversity, evolution and speciation are the results of complex interactions among geographical history, random genetic drift, the environment, biological factors, and stochastic processes (Hoskin, Higgie, Mcdonald, & Moritz, ; Kano, Nishida, & Nakajima, ; Komaki et al, ; Saito & Tojo, ; Schoville, Uchifune, & Machida, ; Su, Wang, & Villanueva, ; Suzuki, Kitano, & Tojo, ). In particular, the fragmentation of populations is one of the major factors driving diversification and speciation often as the result of (a) climate changes within habitats and (b) changes in the environmental conditions between habitats thereby promoting divergent adaptation (Cole et al, ; Jensen et al, ; Schoville & Roderick, ; Shi, Ji, Liu, Wang, & Zhang, ; Stewart, Lister, Barnes, & Dalén, ; Tojo et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Komaki et al suggested that there are two possibilities for terrestrial animal transoceanic dispersal, ocean flow or carry by other animals with high dispersal ability (birds or human) [41]. However, at that time (around 4 mya) humans did not exist yet [42].…”
mentioning
confidence: 99%
“…Zoologists explained that insects, mammals, and reptiles have been demonstrated the transoceanic dispersal by rafting [43][44][45]. Some floating stuff such as macroalgae, pumice, wood, and vegetation could be a substrate for the snake to hold up [41,46]. The ocean drift usually following the ocean throughflow and winds [46].…”
mentioning
confidence: 99%